Reality Television and the Doing of Hyperauthentic Masculinities. Issue 2 (June 2019) - Alexander, Susan M.; Woods, Katie
This study examines American masculinity as constructed in 136 reality television programs airing between 1948 and 2016 with an all-male or predominately male cast. We argue that televised reality programs reveal a new form of hegemonic American masculinity, namely, hyperauthentic masculinity. Hyperauthentic masculinity appears to be grounded in essential male traits, but is rather a reflexive process allowing White male viewers to imagine (re)creating a White male utopia in which they have economic and cultural dominance. Unlike previous studies that claim that reality television allows men to escape into a frontier masculinity of the past, we argue these programs encourage White men today to actively do masculinity and, more important, to believe doing hegemonic masculinity is desirable and worth fighting for.